1989
DOI: 10.1111/j.1751-0813.1989.tb09779.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin containing cells in normal and inflamed accessory sex glands of bulls

Abstract: The peroxidase-antiperoxidase (PAP) technique was used to identify cytoplasmic immunoglobulins in the accessory sex glands of 15 normal bulls and 13 bulls with inflammation of the ASG. Immunoglobulin containing cells (ICC) of the types IgA, IgM, total IgG, IgG1 and IgG2 were measured and their percentages expressed. In accessory sex glands from normal bulls, IgA containing cells were the most frequent in prostate and bulbourethral glands (86.7% and 86.1%, respectively of all ICC present) whereas in the ampulla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The distribution of IgCC in control and infected sheep glands observed in this work is consistent with the findings demonstrated in bulls, where IgCC are also not found or are present in a very limited number in the seminal vesicles of normal animals (Campero et al 1989(Campero et al , 1990, while in the presence of an inflammatory response in the genital tract, IgCC appear in the ampullae and the seminal vesicles (Campero et al 1989). It has been noted that the production of IgA and IgG in the seminal vesicles in the bull is an essential component of the local immune response (Bier et al 1977).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The distribution of IgCC in control and infected sheep glands observed in this work is consistent with the findings demonstrated in bulls, where IgCC are also not found or are present in a very limited number in the seminal vesicles of normal animals (Campero et al 1989(Campero et al , 1990, while in the presence of an inflammatory response in the genital tract, IgCC appear in the ampullae and the seminal vesicles (Campero et al 1989). It has been noted that the production of IgA and IgG in the seminal vesicles in the bull is an essential component of the local immune response (Bier et al 1977).…”
Section: Discussionsupporting
confidence: 80%
“…However, in contrast with the results of this work, these authors found high percentages of IgG-containing-cells, a condition that only occurred in a small number in the IE group in the seminal vesicles and ampullae with active inflammatory processes. This difference may be attributed to the fact that the animals used by Foster et al (1988), had subclinical alterations of the reproductive system with local infection, since no bacteriological examinations of the semen were carried out and they only verified that the animals were free of B. ovis by serology; they also do not distinguish between young animals and adult animals, and variations are likely to occur in the amount and distribution of IgCC due to age, as has been reported in bulls (Campero et al 1989).…”
Section: Discussionmentioning
confidence: 99%